ANALISIS PERBANDINGAN PENDAPATAN USAHATANI TUMPANGSARI JAGUNG DAN KACANG TANAH DENGAN MONOKULTUR JAGUNG DI KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL - Siti Kholizah Lubis; Ari Astuti; Susi Widiatmi (Fakultas Pertanian UST, 2019)
This reseach aims to compare of income from cropping patterns of intercropping of maize and peanuts with corn monoculture in sub-district Ponjong. The method of determining the research area was purposive sampling while in the method of sampling using simple random sampling with a number of 65 respondents namely 42 farmers intercropping corn - peanuts and 23 farmers of monoculture corn. Data analysis methods used are income analysis and efficiency analysis by testing the hypothesis using the t test. The results showed that the income of intercropping maize-peanut farming was Rp. 19.341.850 / ha with an average land area (0,28) ha greater than the income of corn monoculture farming is Rp 9.086.973 / ha with an average land area (0,26) ha. While the efficiency analysis shows that the income of intercropping corn - peanut farming with an R/C Ratio of 4.16 and monoculture jag farming with an R / C Ratio of 2.57. T test results between farm income of intercropping corn-peanuts and corn monoculture farming showed that the t-count was 4.4095 and t-table 1.669 with Î± = 0.05 while the t-test on R / C Ratio with t-value of 5.257 and t-table 1.669 with Î± = 0.05. Farming of intercropping systems of corn-peanut is more efficient compared to corn monoculture farming pattern.Â